Fundamental and Speculative Demands for Housing - Lian, Weicheng (IMF Working Papers; Working Paper ;, 2019)
This paper separates the roles of demand for housing services and belief about future house prices in a house price cycle, by utilizing a feature of user-cost-of-housing that it is sensitive to demand for housing services only. Optimality conditions of producing housing services determine user-cost-of-housing and the elasticity of substitution between land and structures in producing housing services. I find that the impact of demand for housing services on house prices is amplified by a small elasticity of substitution, and demand explained four fifths of the U.S. house price boom in the 2000s.